2006
DOI: 10.1111/j.1474-8673.2006.00375.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term streptozotocin‐induced diabetes alters prostanoid production in rat aorta and mesenteric bed

Abstract: Vascular disease is a major cause of mortality and morbidity in chronic diabetes mellitus. Prostanoids, metabolites of arachidonic acid, include vasoactive substances produced and released from the vascular wall. Alterations in prostanoid production have been reported in the vasculature of diabetic humans and experimental animals. The aim of the present work was to study the influence of three different periods of long-term streptozotocin-induced diabetes, 30, 120 and 180 days in the production of prostanoids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 18 publications
1
15
0
1
Order By: Relevance
“…In diabetic rats, a decrease of prostacyclin and PGE 2 synthesis was reported in the aorta and mesenteric vascular bed [11,12]. Previous studies indicate that the levels of these prostaglandins remain unchanged in the coronary vessels of diabetic rats [13], while increased prostacyclin production has been shown in diabetic mice aorta [9].…”
Section: Discussionmentioning
confidence: 96%
“…In diabetic rats, a decrease of prostacyclin and PGE 2 synthesis was reported in the aorta and mesenteric vascular bed [11,12]. Previous studies indicate that the levels of these prostaglandins remain unchanged in the coronary vessels of diabetic rats [13], while increased prostacyclin production has been shown in diabetic mice aorta [9].…”
Section: Discussionmentioning
confidence: 96%
“…Impairment of endothelial function may contribute to the pathogenesis of cardiovascular complications induced by diabetes . Some of the mechanisms leading to these impairments in diabetes may include factors that decrease endothelium‐derived relaxation factors, such as NO and prostacyclin . It has been shown that endothelium‐derived NO is reduced in the diabetic milieu and that NO‐dependent vasodilation is reduced by oxidative stress, thereby impairing endothelial function .…”
Section: Discussionmentioning
confidence: 99%
“…The possible explanations given for the development or not of vascular dysfunction in diabetes can be related to different glucose concentrations in the media during the vascular reactivity study (44), the duration of diabetes, the vascular bed (44)(45)(46), and the studied species (44,45). We credit the failure in the vascular dysfunction development of our model to insufficient diabetes duration, which was reinforced by a recent report showing that diabetes lasting 4 weeks does not promote vascular dysfunction, whereas diabetes lasting 8 weeks causes endothelium-dependent and independent relaxation impairment (17).…”
Section: Discussionmentioning
confidence: 99%